2017
DOI: 10.1186/s13104-016-2353-3
|View full text |Cite
|
Sign up to set email alerts
|

Invasive pneumococcal disease caused by mucoid serotype 3 Streptococcus pneumoniae: a case report and literature review

Abstract: BackgroundAmong the different serotypes of Streptococcus pneumoniae, serotype 3 has received global attention. We report the fatal case of a 76-year-old Japanese man who had an invasive pneumococcal disease associated with pneumonia caused by serotype 3 S. pneumoniae.Case presentationThe patient had a history of hypertension, laryngeal cancer, chronic obstructive pulmonary disease, and type 2 diabetes mellitus. Following a cerebral arteriovenous malformation hemorrhage, he underwent surgery to remove the hemat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
19
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(24 citation statements)
references
References 17 publications
(21 reference statements)
2
19
0
1
Order By: Relevance
“…27 However, in line with other studies, we have found serotypes 3 to be a frequent cause of non-IPD. 28,29 Serotypes 3 and 19A are not recently covered by PCV-10, thus using these vaccines may not be sufficient. The data showed low serotype coverage of PCV-7 (50%) in period II which is in concordance with data from other Asian countries such as Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…27 However, in line with other studies, we have found serotypes 3 to be a frequent cause of non-IPD. 28,29 Serotypes 3 and 19A are not recently covered by PCV-10, thus using these vaccines may not be sufficient. The data showed low serotype coverage of PCV-7 (50%) in period II which is in concordance with data from other Asian countries such as Nepal.…”
Section: Discussionmentioning
confidence: 99%
“…Полимерные цепи целлобиуроновой кислоты капсулы S. pneumoniae серотипа 3 ковалентно не связаны с клеточной стенкой, в отличие от других серотипов пневмококка (кроме серотипа 37) [18], и характеризуются тенденцией образовывать при росте на агаре мукоидные колонии [19,20]. Мукоидные штаммы S. pneumoniae серотипа 3 вызывают тяжелые заболевания, характеризующиеся менее успешным и более длительным лечением по сравнению с немукоидными серотипами и нередко заканчивающиеся летально [14,21,22]. В настоящее время накопилось значительное количество данных, свидетельствующих о недостаточной иммуногенности КП S. pneumoniae серотипа 3 в составе пневмококковых вакцин, и дискуссии по этому вопросу продолжаются.…”
Section: серотип 3-ассоциированные заболеванияunclassified
“…Mortalities are mainly due to pneumococcal pneumonia (81%) with the rest attributed to meningitis (12%), bacteraemia, and sepsis (7%) [2][3][4]. Even with modern antimicrobial treatment, survivors of invasive pneumococcal diseases Vaccines 2020, 8,187 2 of 20 usually develop long term complications such as hearing loss and neuropsychological impairments [5]. Still, these alarming figures of pneumococcal morbidity and mortality might underestimate the actual burden of pneumococcal diseases because many developing countries lack sensitive diagnostic tests for detecting the disease aetiology.…”
Section: Introductionmentioning
confidence: 99%
“…The use of these vaccines has led to a considerable reduction in mortality ascribed to pneumococcal infections [2]. These vaccines are designed to generate antibodies against the capsular polysaccharide of the pneumococcus [6] which is structurally distinct among S. pneumoniae strains [7,8]. Currently used PCVs were initially designed for use in Western industrialized countries.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation